Genetic Diversity of Salt Tolerance in Miscanthus - Chen, Chang-Lin; van der Schoot, Hanneke; Dehghan, Shiva; Alvim Kamei, Claire L.; Schwarz, Kai-Uwe; Meyer, Heike; Visser, Richard G. F.; van der Linden, C. Gerard (Frontiers in Plant Science, 2017)
Miscanthus is a woody rhizomatous C4 grass that can be used as a CO2 neutral biofuel resource. It has potential to grow in marginal areas such as saline soils, avoiding competition for arable lands with food crops. This study explored genetic diversity for salt tolerance in Miscanthus and discovered mechanisms and traits that can be used to improve the yield under salt stress. Seventy genotypes of Miscanthus (including 57 M. sinensis, 5 M. sacchariflorus and 8 hybrids) were evaluated for salt tolerance under saline (150 mM NaCl) and normal growing conditions using a hydroponic system. Analyses of shoot growth traits and ion concentrations revealed the existence of large variation for salt tolerance in the genotypes. We identified genotypes with potential for high biomass production both under control and saline conditions that may be utilized for growth under marginal, saline conditions. Several relatively salt tolerant genotypes had clearly lower Na+ concentrations and showed relatively high K+/Na+ ratios in the shoots under salt stress, indicating that a Na+ exclusion mechanism was utilized to prevent Na+ accumulation in the leaves. Other genotypes showed limited reduction in leaf expansion and growth rate under saline conditions, which may be indicative of osmotic stress tolerance. The genotypes demonstrating potentially different salt tolerance mechanisms can serve as starting material for breeding programs aimed at improving salinity tolerance of Miscanthus.